Analysis of Multi-Phase Mixed Slurry Horizontal Section Migration Efficiency in Natural Gas Hydrate Drilling and Production Method Based on Double-Layer Continuous Pipe and Double Gradient Drilling - Yang Tang; Jiaxin Yao; Guorong Wang; Yin He; Peng Sun (Energies, 2020)
In order to improve the recovery efficiency of natural gas hydrate in solid-state fluidized mining of natural gas hydrate, we solve drilling safety problems, such as narrow density of natural gas hydrate formation pressure window and poor wellbore stability caused by high upstream velocity during drilling and production. In this study—in order to increase the natural gas hydrate output and reduce production costs—based on the principle of the solid-state fluidized mining, a natural gas hydrate drilling method based on double-layer continuous-pipe double-gradient drilling was proposed to solve the above problems. The article introduces a drilling and production tool combination scheme and the mathematical model of wellbore-pressure dynamic regulation. Simulation software was used to study and compare the migration efficiency of multiphase mixed slurries of sediment and natural gas hydrates in the horizontal section of the double-layer continuous-pipe double-gradient drilling method and traditional drilling method. The results show that the transport efficiency of the multiphase mixed slurry of sediment and natural gas hydrate in the horizontal section of the double-layer continuous-pipe double-gradient drilling method is better than the traditional drilling method under the same conditions. When the double-layer continuous-pipe double-gradient drilling method is adopted, the multiphase mixed slurry of sediment and natural gas hydrate is transported in the pipe and has the function of the submarine lift pump, which effectively avoids the problem of the stability of the shaft wall caused by excessive flow velocity. This will also be more suitable for the transportation of large-diameter particles during the solid-state fluidized mining of natural gas hydrates.